Cellular and metabolic effects of renin-angiotensin system blockade on glycogen storage disease type I nephropathy. Issue 6 (7th October 2021) - Monteillet, Laure; Labrune, Philippe; Hochuli, Michel; Do Cao, Jeremy; Tortereau, Antonin; Miliano, Alexane Cannella; Ardon-Zitoun, Carine; Duchampt, Adeline; Silva, Marine; Verzieux, Vincent; Mithieux, Gilles; Rajas, Fabienne
Abstract: Glycogen Storage Disease Type I (GSDI) is an inherited disease caused by glucose-6 phosphatase (G6Pase) deficiency, leading to a loss of endogenous glucose production and severe hypoglycemia. Moreover, most GSDI patients develop a chronic kidney disease (CKD) due to lipid accumulation in the kidney. Similar to diabetic CKD, activation of renin-angiotensin system (RAS) promotes renal fibrosis in GSDI. Here, we investigated the physiological and molecular effects of RAS blockers in GSDI patients and mice. A retrospective analysis of renal function was performed in 21 GSDI patients treated with RAS blockers. Cellular and metabolic impacts of RAS blockade were analyzed in K.G6pc −/− mice characterized by G6pc1 deletion in kidneys. GSDI patients started RAS blocker treatment at a median age of 21 years and long-term treatment reduced the progression of CKD in about 50% of patients. However, CKD progressed to kidney failure in 20% of treated patients, requiring renal transplantation. In K.G6pc −/− mice, CKD was associated with an impairment of autophagy and ER stress. RAS blockade resulted in a rescue of autophagy and decreased ER stress, concomitantly with decreased fibrosis and improved renal function, but without impact on glycogen and lipid contents. In conclusion, these data confirm the partial beneficial effect of RAS blockers in the prevention of CKD in GSDI. Mechanistically, we show that these effects are linked to a reduction of cell stress, without affecting metabolism.